Answer:
h(x - 1) = -5x - 2
General Formulas and Concepts:
<u>Pre-Algebra</u>
<u>Algebra I</u>
Terms/Coefficients
Functions
Step-by-step explanation:
<u>Step 1: Define</u>
<em>Identify</em>
h(x) = -5x - 7
<u>Step 2: Find</u>
- Substitute in <em>x </em>[Function h(x)]: h(x - 1) = -5(x - 1) - 7
- [Distributive Property] Distribute -5: h(x - 1) = -5x + 5 - 7
- Combine like terms: h(x - 1) = -5x - 2
18 ÷ (2/3) = 18 × (3/2) = 18×3/2 = 9×3 = 27
The answer is 27
Answer:
−7k^4−11k^2+6
Step-by-step explanation:
−4k^4+14+3k^2−3k^4−14k^2−8
(−4k^4+−3k^4)+(3k^2+−14k^2)+(14+−8)
−7k^4−11k^2+6
...
Step-by-step explanation:
<em><u>I </u></em><em><u>thin</u></em><em><u>k</u></em><em><u> </u></em><em><u>mode</u></em><em><u>,</u></em><em><u>range</u></em><em><u> </u></em><em><u>and</u></em><em><u> </u></em><em><u>median</u></em><em><u> </u></em><em><u>dpo</u></em><em><u> </u></em><em><u>ako</u></em><em><u> </u></em><em><u>sure</u></em>